Effects of electron-withdrawing group and π-conjugation length in donor-acceptor oligothiophenes on their properties and performance in non-fullerene organic solar cells. (October 2021) - Kalinichenko, Nadezhda K.; Balakirev, Dmitry O.; Savchenko, Petr S.; Mannanov, Artur L.; Peregudova, Svetlana M.; Paraschuk, Dmitry Yu.; Ponomarenko, Sergey A.; Luponosov, Yuriy N.
Abstract: The development of small-molecule donor materials for highly efficient non-fullerene (NF) organic solar cells (OSC) remains an urgent research task. In this work, the synthesis of donor-acceptor molecules containing either five (5T) or seven (7T) thiophene units end-capped with methyl dicyanovinyl (DCV) or ethyl cyanoacetate (CNA) electron-withdrawing groups was reported. Their thermal stability, phase behaviour, optical and electrochemical properties as well as photovoltaic performance in blends with IDIC or Y6 as acceptor materials were comprehensively investigated and compared. All of the obtained donor molecules are characterized by high thermal stability, efficient sunlight absorption and excellent solubility in combination with a good crystallinity. The results obtained allowed us to reveal the impact of the oligothiophene conjugation length and type of electron-withdrawing group on the properties and performance of the D-A oligothiophenes in NF OSC. The results clearly demonstrate that the devices based on donor molecules with 7T or CNA fragments significantly outperform those based on 5T or DCV groups. Graphical abstract: Image 1 Highlights: Donor quinque- (5T) and septithiophenes (7T) with two types of acceptor groups are reported. Alkyl-dicyanovinyl (DCV) groups are favorable to design stable donor oligothiophenes. 7T outperforms 5T counterparts in blends with IDIC or Y6 non-fullerene (NF) acceptors. Molecules with cyanoacetate acceptor groups outperform counterparts with DCV in NF OSC.